Effects of External Abdominal Pressure Support on Dynamic Balance: A Randomized Crossover Study - Yuki Nakai; Takara Kijimuta; Yasufumi Takeshita; Ryoji Kiyama; Sota Araki; Takasuke Miyazaki; Masayuki Kawada (MDPI AG, 2023)
Abdominal pressure is vital in protecting the lumbar spine and controlling postural balance. Dynamic balance is associated with movement stability, adaptation to load, and reduced injury risk. Although trunk stability has been examined using belts and braces, the effects of external abdominal pressure support (APS) on balance control remain unknown. In this study, we aimed to determine the effects of external APS on dynamic balance. Overall, 31 young adults participated in this randomized crossover study. External APS was provided using a device that could be pressurized and decompressed by inflating a cuff belt wrapped around the trunk. The modified Star Excursion Balance Test was performed under external APS and non-APS conditions. The maximum anterior, posterolateral, and posteromedial values normalized to the spinal malleolar distance and their respective composite values were compared between the two conditions with and without APS. Posterolateral, posteromedial, and composite values were significantly higher in the APS condition than in the non-APS condition (p < 0.001). The external APS was effective in immediately improving dynamic balance. Furthermore, APS was effective in dynamic balance control as it improved stability during anterior trunk tilt, which displaces the center of gravity forward.